Extensive deep neck abscess caused by middle ear cholesteatoma complicating Proteus vulgaris infection: A case report and literature review - Jin, Mengru; Zhu, Zeyu; Zhou, Peng; Liu, Shixi (Medicine (Baltimore), 2025)
Rationale: Middle ear cholesteatoma (MEC) is a non-neoplastic cystic lesion that can cause severe complications if untreated. While subperiosteal abscesses, neck abscesses, and sigmoid sinus thrombophlebitis have been reported, an extensive deep neck abscess extending to the axillary fossa due to MEC has not been previously documented. This case highlights a deep neck abscess complicated by Proteus vulgaris infection during coronavirus disease 2019 (COVID-19) recovery, underscoring the importance of individualized management strategies based on pathogen characteristics. Patient concerns: A 27-year-old man with a history of left ear purulent otorrhea for > 20 years presented with neck swelling for 5 days during COVID-19 recovery. Diagnoses: Examination revealed: the left neck, up to the mastoid process, down to the ipsilateral armpit and lateral chest wall, and back to the trapezius muscle, was widely erythematous and swollen, with elevated skin temperature. Computed tomography revealed soft tissue density shadows in the left mastoid process, along with gas and pus accumulation in the left neck, pharynx, and axillary fossa. Culture results confirmed P vulgaris infection. The diagnosis was MEC complicated by a deep neck abscess and P vulgaris infection. Interventions: The patient underwent a modified radical mastoidectomy and incision and drainage of a left maxillofacial cervical multi-gap abscess. Postoperatively, the neck cavity was sutured, and negative pressure drainage tubes were placed. Due to subsequent parapharyngeal swelling and respiratory distress with a difficult airway, a tracheotomy was performed, followed by additional drainage of an abscess in the posterior oropharyngeal wall. Extensive necrosis of the cervical soft tissue necessitated reopening the neck incision and placement of Penrose drains for continued drainage. Outcomes: The patient recovered well following surgical interventions and tailored wound management, with no further complications. Lessons: This case underscores the importance of timely and appropriate abscess drainage and wound management tailored to the causative organism's characteristics. It also highlights the need for aggressive treatment of the primary pathology (MEC) to prevent severe complications. Clinicians should be vigilant for unusual presentations of deep neck abscesses, especially in patients with recent infections such as COVID-19, which may complicate the clinical course.